2018
DOI: 10.1159/000487507
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Fecoflowgram for Assessment of Defecation after Intersphincteric Resection

Abstract: Aim: We have developed an imaging functional assessment of defecation after partial intersphincteric resection (ISR) by fecoflowgram obtained by defecography. Patients and Methods: Between January 2012 and December 2014, 6 patients with temporary ileostomy who underwent partial ISR for lower rectal cancer at our hospital were enrolled in this study. Defecography was performed 2 weeks after closure of the ileostomy. The defecation of all patients was evaluated by defecography and a fecoflowgram calculated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Kitaguchi et al [ 85 ] found that maximum resting pressure and maximum squeeze pressure were significantly lower after ISR, and an elevated incidence of severe FI after ISR was independently related to a high pressure zone before ISR ≤ 3 cm and MRP before ISR > 60 mmHg. Lately, the fecoflowgrams calculated from defecography has also been a promising assessment of defecation after ISR [ 86 ]. Functional results after ISR reported by several studies [ 7 , 11 , 60 , 80 , 87 99 ] have been summarized in Tables 3 and 4 .…”
Section: Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kitaguchi et al [ 85 ] found that maximum resting pressure and maximum squeeze pressure were significantly lower after ISR, and an elevated incidence of severe FI after ISR was independently related to a high pressure zone before ISR ≤ 3 cm and MRP before ISR > 60 mmHg. Lately, the fecoflowgrams calculated from defecography has also been a promising assessment of defecation after ISR [ 86 ]. Functional results after ISR reported by several studies [ 7 , 11 , 60 , 80 , 87 99 ] have been summarized in Tables 3 and 4 .…”
Section: Functional Outcomesmentioning
confidence: 99%
“…High-resolution anorectal manometry (HR-ARM) is reliable for the evaluation of anal function after ISR objectively and accurately, and the high pressure zone and maximum resting pressure (MRP) may be useful [85] found that maximum resting pressure and maximum squeeze pressure were significantly lower after ISR, and an elevated incidence of severe FI after ISR was independently related to a high pressure zone before ISR ≤ 3 cm and MRP before ISR > 60 mmHg. Lately, the fecoflowgrams calculated from defecography has also been a promising assessment of defecation after ISR [86]. Functional results after ISR reported by several studies [7,11,60,80,[87][88][89][90][91][92][93][94][95][96][97][98][99] have been summarized in Tables 3 and 4.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Defecational functions consist of two main factors. One is motional function, which is evaluated by defecography, and the other is time course of pressure distribution during defecation which is evaluated by fecoflowgram [11].…”
Section: Discussionmentioning
confidence: 99%